ANALISIS FAKTOR YANG MEMPENGARUHI TENAGA KERJA KONSTRUKSI UNTUK MEMILIKI SKA/SKTK PADA KONTRAKTOR DI KABUPATEN BADUNG - I M. Jelantik; I M. Alit K. Salain; Mayun Nadiasa (JURNAL SPEKTRAN, 2014)
The law of construction service (UUJK) No.18 Year 1999 has required that the manpower of construction has to have the Certificate of Expertise (SKA) and Working Skill (SKTK).  The purpose is in order that the business of construction service in Indonesia becomes firm, reliable, has high competiveness and produces a high quality construction work. But there is still lot of manpower of construction that has not has it. This research has purpose to find out the factors that influence the manpower of construction on contractor in Badung Regency to have SKA/SKTK. Sample to be researched is the manpower of construction at the contractor of project manager of Badung Regency Government with qualification grade 2, 3, 4, 5 and 6.  Data is obtained by spreading out questionnaire and interview.  The data analysis and processing is using the factor analysis. Research result is that there are three factors that are identified to have influenced the manpower of construction to have the SKA/SKTK.  These three factors are factor I, II and III. These three factors are formed by fifteen variables.  The most dominant factor is the factor I.  This factor is formed by seven variables those are it still be able to have job without having the SKA/SKTK, the SKA/SKTK is not fully required on the government’s project, the SKA/SKTK is not yet required on non-government’s project, to already have the SKA/SKTK cannot guarantee that the wage/salary will be increased, to already have the SKA/SKTK cannot guarantee the increasing of career level, to already have the SKA/SKTK cannot guarantee the increasing of expertise/work skill.